Bòsò Walikan Malang’s address practices - Yannuar, Nurenzia; Iragiliati, Emalia; Zen, Evynurul Laily (Penerbit Universiti Kebangsaan Malaysia, 2017)
Address practices in natural conversations are sociolinguistically significant, because they display speakers’ socio-cultural values as well as the community’s social structure and social change. Focusing on Bòsò Walikan Malang1 (/bɔsɔ waliʔan malaŋan/, hereafter referred to as Walikan), a youth language spoken in Malang, this paper examines how address terms and politeness are practiced in a multilingual setting. Walikan is a colloquial variety of local Javanese and Indonesian that features word reversing (mlaku > uklam ‘to walk’; makan > nakam ‘to eat’). The youth language was specifically chosen as the focus of this study because it is an important symbol of the socio-cultural identity of the Arema (Arek Malang; the people of Malang). Looking at the underexplored topic of speech levels in youth language, the current research discusses the value of Walikan’s address terms and how they are currently used to demonstrate the speakers’ linguistic politeness. The analysis compares Walikan’s address terms with those of Javanese and Indonesian, two dominant languages spoken in the area. Data for the current study were drawn from recordings, interviews, and observations conducted in an extensive fieldwork. The results of this study reveal a speakers’ shift of value that is mainly prompted by a compromised common ground and social distance. The study argues that address practices in Walikan show different degree of politeness than that of Javanese and Indonesian.